Marcel Dzama : sower of discord. - Dzama, Marcel; Bailey, Bradley; Eggers, Dave; Jonze, Spike; Pettibon, Raymond (New York : Abrams, 2013)
This monograph is the definitive publication to date on the internationally renowned Canadian artist Marcel Dzama. Characterised by an immediately recognisable cast of fanciful and frightening characters, Dzama's work draws from a diverse range of references and artistic influences, including Dada and Marcel Duchamp. While the artist is best known for his delicate, psychosexual drawings, rendered in a distinctive palette of muted colors, his work also includes sculpture, painting, film and dioramas. More than 300 colour images from the late 1990s through the present trace the artistic evolution and tremendous talent of this prolific and highly acclaimed young artist. Textual contributions include five original short stories related to Dzama's work by foreword by best-selling author Dave Eggers, an essay by Duchamp scholar and art historian Bradley Bailey, an essay by contemporary artist Raymond Pettibon and an interview with renowned filmmaker and friend Spike Jonze.
Essays by Bradley Bailey, Dave Eggers; includes the artist's interview with Spike Jonze.
boek
Keywords: Dzama Marcel